2022
DOI: 10.1016/j.compedu.2021.104408
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging gameful experience in digital game-based learning: A double-mediation model of perceived instructional support, group engagement, and flow

Abstract: In the current digitalization era, digital game-based learning (DGBL) is used in education to engage and motivate students. Gameful experience (GE) is a crucial precondition to determine the effectiveness of these games. However, previous research focused solely on the effects of games on inter alia student engagement, and empirical research regarding GE is lacking. This study investigates the factors that encourage students' GE. Grounded in the theory of experience, a double-mediation model is developed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 92 publications
0
9
0
2
Order By: Relevance
“…Regarding cognition, some scholars have revealed that game-based learning can improve learners’ creativity (e.g., Behnamnia et al, 2020), knowledge comprehension (e.g., Holzer et al, 2020; Vlachopoulos & Makri, 2017), or academic performance (e.g., Zainuddin et al, 2020). Regarding the affective aspect, some scholars have found that game-based learning can help improve learners’ learning motivation (e.g., Bai et al, 2020; Höyng, 2022; Liu et al, 2023). Regarding skills, some scholars deemed that game-based learning may improve learners’ problem-solving skills (e.g., (Liu & Israel, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding cognition, some scholars have revealed that game-based learning can improve learners’ creativity (e.g., Behnamnia et al, 2020), knowledge comprehension (e.g., Holzer et al, 2020; Vlachopoulos & Makri, 2017), or academic performance (e.g., Zainuddin et al, 2020). Regarding the affective aspect, some scholars have found that game-based learning can help improve learners’ learning motivation (e.g., Bai et al, 2020; Höyng, 2022; Liu et al, 2023). Regarding skills, some scholars deemed that game-based learning may improve learners’ problem-solving skills (e.g., (Liu & Israel, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of DEG has the same educational impact as a conventional exercise session guided by a teaching assistant (De Troyer et al, 2019). Furthermore, the relationship between teaching support and student experience is positively influenced by group participation (Hoyng, 2022). The DEG technique is equivalent to conventional ways of learning in terms of overall and immediate gains, although conventional lectures seem to be more successful in enhancing students' short-term and long-term knowledge (Rondon et al, 2013).…”
Section: Rq1mentioning
confidence: 99%
“…-Flow is an experience of utter and total absorption in the activity (Höyng 2022, Silva et al 2019).…”
Section: Introductionmentioning
confidence: 99%